The "Make Your Own Religion" Project - Bauman, Chad M. (Teaching theology and religion, 2016)
The "Make Your Own Religion" class project was designed to address a perceived need to introduce more theoretical thinking about religion into a typical religion survey course, and to do so in such a way that students would experience the wonder of theoretical discovery, and through or because of that discovery hopefully both better retain knowledge gained from the project and nurture within themselves the practice of thinking more analytically about religion (and other social and cultural things). Despite a number of challenges and unresolved questions associated with the project, it has proven relatively successful at introducing and provoking theoretical thinking about religion in a compressed period of time, without taking an inordinate number of class periods away from the survey itself. A brief description and analysis of the assignment is followed by four short responses.